PERCEPTION AND SATISFACTION LEVEL TOWARDS CSR ON SLUM DEVELOPMENT - MATHIRAJ, Dr.SP.; BHARATHI, M.THIVYA (International Journal of Psychosocial Rehabilitation, 2020)
Integration of CSR in business is a vital part. Hence stake holders instead of thinking about profit & growth, corporate must think and contribute to the societies, Environment & importantly to their labors in terms of any forms. So it’s giving lots of meaning to all the aspects, not only limited to profit & growth in business. As for as this topic is concern, we must know the facts behind slum development in developing countries like India. Rural peoples are moving from their native place to urban location rapidly because of their basic needs such as Education, Employment, Business & Good Medical facilities. Rural people’s life depending with agriculture but nowadays due to global warming, farmers are not getting sufficient rain to produce enough yields. Second thing farmers are not getting proper cost for their produced agricultural items. Because the Government not allocating the sufficient funds to agricultures. Rural people don’t have an option to move from their location to urban. The study will be analyzed the Perception and satisfaction of CSR on slum development. This paper analyzed the Descriptive statistics, factor analysis and ANOVA.